Еліпсометрична діагностика поверхневого шару оптичного скла - Makarenko, O. V.; Poperenko, L. V.; Zavalistyi, O. I.; Yampolskiy, A. L. (Publishing house "Academperiodika", 2019)
Optical properties of a transient layer with a broken structure that arises at the surface of optical glass at its treatment have been considered. Rather often, the surface of optical elements is considered to be perfect, although the actual inhomogeneous surface structure can have a significant effect for precision physical experiments or novel technological problems. Furthermore, the simulation of the surface layer structure and the corresponding optical characteristics, as well as the study of a possibility to determine those parameters from the results of optical researches, is also of theoretical interest, which is demonstrated in this work. Ellipsometric measurements of optical glass specimens with a broken surface layer are carried out. When modeling the angular dependences of the ellipsometric parameters tan ф and cos б, the near-surface specimen region is considered as a stack of 500 thin layers, and the matrix method of light reflection in this structure with regard for the interference phenomenon is used in calculations. Five models are tested for the optical profile of a nonuniform layer, whose parameters are fitted to achieve the minimum of the target function describing the discrepancy between the calculated and measured data. It is found that the theoretical models describe the optical properties of the specimens more accurately, if they make allowance for the inhomogeneous surface layer. Nevertheless, the solution of the inverse ellipsometric problem turns out ambiguous, so that additional measurements are required for the final choice of a model that would be adequate to the actual morphological structure of the broken layer to be made. However, the key advantage of the applied method consists in that it allows a direct registration of the optical response of the system.